Exploring peace and conflict dynamics in climate smart villages: Assessing co- benefits and risks of climate adaptation practices in West Africa - Renkamp, Theresa; Sarzana, Carolina; Ramos, Cristina; Cisse, Sokhna Ramatoulaye (2024)
This fieldwork report outlines the methodology and presents preliminary findings from a study examining the peace and conflict outcomes of the Climate Smart Village (CSV) project in Kaffrine, Senegal. The study aims to build evidence for the CSV+ approach, which integrates peace co-benefits—such as social cohesion, trust, and institutional strengthening—into climate adaptation strategies. Drawing on mixed-methods data collection, including a survey (n=345), qualitative interviews, and focus group discussions, the findings highlight the critical importance of incorporating conflict sensitivity into climate adaptation interventions to promote climate-resilient peace and prevent the exacerbation of existing community tensions.